Enhanced toxicity of 'bulk' titanium dioxide compared to 'fresh' and 'aged' nano-TiO2 in marine mussels (Mytilus galloprovincialis). Issue 5 (August 2014) - D'Agata, Alessia; Fasulo, Salvatore; Dallas, Lorna J.; Fisher, Andrew S.; Maisano, Maria; Readman, James W.; Jha, Awadhesh N.
Abstract Marine bivalves (Mytilus galloprovincialis) were exposed to titanium dioxide (10 mg L−1) either as engineered nanoparticles (nTiO2; fresh, or aged under simulated sunlight for 7 days) or the bulk equivalent. Inductively coupled plasma-optical emission spectrometry analyses of mussel tissues showed higher Ti accumulation (>10-fold) in the digestive gland compared to gills. Nano-sized TiO2 showed greater accumulation than bulk, irrespective of ageing, particularly in digestive gland (>sixfold higher). Despite this, transcriptional expression of metallothionein genes, histology and histochemical analysis suggested that the bulk material was more toxic. Haemocytes showed significantly enhanced DNA damage, determined by the modified comet assay, for all treatments compared to the control, but no significant differences between the treatments. Our integrated study suggests that for this ecologically relevant organism photocatalytic ageing of nTiO2 does not significantly alter toxicity, and that bulk TiO2 may be less ecotoxicologically inert than previously assumed.